Real effects of credit supply shocks: Evidence from Danish banks, firms, and workers - Simon Juul Hviid; Christofer Schroeder (European Central Bank (ECB), 2024)
Contractions in credit supply can lead firms to reduce their level of employment, yet little is known about how these shocks affect the composition of firms' employees and outcomes at the worker level. This paper investigates how bank distress affects credit provision and its effects on employment beyond firm-level aggregates. To do so, we use a novel dataset built from administrative and tax records linking all banks, firms, and workers in Denmark. We show that banks that were particularly exposed to the 2008-09 financial crisis cut lending to firms, and firms were unable to fully compensate with financing from alternate sources. The decrease in credit supply led to a drop in firm-level employment, with effects concentrated among firms with low pre-crisis liquidity, and on employment of low-educated and non-managerial workers. At the worker level, we find that positive effects on unemployment were driven by effects on low-educated, non-managerial and short-tenured workers. Our estimates suggest that cuts in bank lending can account for at least 5% of the fall in employment of low-educated workers in our sample, and are an important factor behind heterogeneous employment dynamics in times of contractionary credit.
Keywords: E24; E44; G01; G21; J23; 330; Bank lending; Firm borrowing; Labour demand; Financial crisis